2019
DOI: 10.1016/j.jcyt.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenicity assessment of cell therapy products: The need for global consensus and points to consider

Abstract: Pluripotent stem cells offer the potential for an unlimited source for cell therapy products. However, there is concern regarding the tumorigenicity of these products in humans, mainly due to the possible unintended contamination of undifferentiated cells or transformed cells. Because of the complex nature of these new therapies and the lack of a globally accepted consensus on the strategy for tumorigenicity evaluation, a case-by-case approach is recommended for the risk assessment of each cell therapy product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 56 publications
0
94
0
Order By: Relevance
“…We will also assess the effect of A83-01 withdrawal and reversibility on global chromatin architectural changes and gene expression, and the effect on cryopreservation and thawing. Functional in vivo assays of sustained A83-01-treated eMSC will be assessed using our xenograft mouse model ( Gurung et al, 2018a ) and in tumorigenicity animal models ( Sato et al, 2019 ). In vitro potency assays that reflect in vivo eMSC function need to be developed, based on their angiogenic and immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…We will also assess the effect of A83-01 withdrawal and reversibility on global chromatin architectural changes and gene expression, and the effect on cryopreservation and thawing. Functional in vivo assays of sustained A83-01-treated eMSC will be assessed using our xenograft mouse model ( Gurung et al, 2018a ) and in tumorigenicity animal models ( Sato et al, 2019 ). In vitro potency assays that reflect in vivo eMSC function need to be developed, based on their angiogenic and immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…The potential risk of tumorigenicity cannot be fully excluded in the present study, although no indication of tumor formation was observed in the analysis. Therefore, long-term follow-up studies and various types of evaluations based on global consensus will be useful to address in the future the possibility of tumorigenicity of transplanted NPCs (Lee et al, 2013;Sato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the utility of these in vitro tests, tumorigenicity studies in animals still represent a major pillar of the preclinical safety assessment. Several factors have then to be taken into consideration, which include the number of cells to be inoculated, the duration of follow-up, the site of transplantation and the limit of detection of the relevant assays (Sato et al, 2019). The choice of the animal model is particularly critical, keeping in mind that most studies entail transplanting human cells into rodents and, as such, should be interpreted cautiously since xenotransplantation is less likely to induce teratomas than allografts (Erdö et al, 2003).…”
Section: A Common Mechanism-independent Issue: Safetymentioning
confidence: 99%